Peran Siswa dalam Kegiatan Palang Merah Remaja terhadap Pembentukan Profil Pelajar Pancasila di MA NW Wanasaba Lombok Timur - Ismul Azam Magani; Edy Herianto; Basariah, Basariah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to explore the role of students in the Red Cross Youth (PMR) extracurricular activities in shaping the Pancasila Student Profile at MA NW Wanasaba, East Lombok. The research employed a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, involving supervisors, trainers, and PMR members as research subjects. The findings reveal that student involvement in PMR significantly contributes to the development of the six dimensions of the Pancasila Student Profile: faith and devotion to God Almighty, global diversity, mutual cooperation, independence, critical reasoning, and creativity. Activities such as social service, blood donation, health service in the school clinic, leadership training, first aid, and disaster simulations foster empathy, responsibility, and leadership skills among students. Supporting factors include adequate facilities, applicable training materials, and the guidance of supervisors and trainers, while the main challenges are time management and student motivation. Therefore, PMR is not only a place for developing skills but also a strategic means of building resilient, caring, and competitive Pancasila students.